SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PEMENANG LELANG TENDER PROYEK MENGGUNAKAN METODE PERBANDINGAN EKSPONENTIAL PADA KANTOR DINAS PEKERJAAN UMUM TIMOR TENGAH UTARA - Deni Alfiando Salem; S Sumarlin (Jurnal Ilmiah Flash, 2022)
Tenders or auctions in the construction industry are often held, either public or open or closed depending on the owner and the project to be carried out. Tenders or auctions are needed because in the implementation of a project, both government projects and private projects, the owner expects the best bid for the project. A tender committee is an organization established and endorsed which is responsible for the successful auction of a tender. The tender or auction in the north middle Timor regency is held every year after the local government proposes the project procurement in the budget session with the DPR. Project procurement is proposed at the hearing in the form of the location and amount of the project budget, during the budget session. The amount of budget proposed by the government can be reduced and the project procurement can be canceled unilaterally by the DPR, after the budget session is over and the project procurement has been approved, the project will be posted on the LPSE (Electronic Procurement Service) website of north middle Timor regency. In determining the tender winner, at the final determination stage, is still done manually so there are a lot of cheats and frequent human errors, therefore an application is needed to assist and facilitate decision-making in determining the winner of the project tender. This research produces a decision support system application to determine the winner of the project tender that can assist the committee in determining decision-making using the Exponential Comparison Method. The result of the system implementation is that the system can assist and facilitate decision-making in determining the project tender winner. The decision support system for determining the winner of this project tender can assist the committee in determining decision-making using the Exponential Comparison Method. Measuring the accuracy of determining the project tender winner between the Public Works Agency ranking with the Exponential Comparison Method (MPE) algorithm ranking, obtained an accuracy rate of 100%, so that the Exponential Comparison Method algorithm is feasible to be implemented in making a decision support system for determining project tender winners at the office North Middle Timor Regency Public Works.